Behavioral Finance in the Digital Era: Understanding Investor Psychology in a High-Volatility Market - Willim, Andre Prasetya (SAFE-Network, 2025)
This study investigates the impact of digital information overload and market sentiment on investment decision-making in the digital era, with investor confidence examined as a mediating variable. Using a quantitative research design and data collected from active retail investors through an online survey, the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results reveal that digital information overload negatively influences both investor confidence and investment decisions, while market sentiment exerts a positive effect on both. Furthermore, investor confidence significantly mediates the relationship between the independent variables and investment decision-making, highlighting its central psychological role in the digital investment environment. These findings enrich the behavioral finance literature by incorporating digital-era constructs and provide actionable insights for financial platforms, educators, and regulators to foster more confident and rational investment behavior in volatile markets.